Comparison of prevalence of schizophrenia among residents of hostels for homeless people in 1966 and 1992. - Geddes, J; Newton, R; Young, G; Bailey, S; Freeman, C; Priest, R (1994)
OBJECTIVE: To determine whether the prevalence of schizophrenia among the homeless population of Edinburgh resident in hostels has changed between 1966 and 1992. DESIGN: Comparison of two cross sectional surveys. SETTINGS: Hostels for homeless people in Edinburgh. SUBJECTS: In 1966 a random sample of 98 residents of three common lodging houses. In 1992 a random sample of 198 residents of nine hostels. MAIN OUTCOME MEASURE: Prevalence of schizophrenia. RESULTS: The prevalence of schizophrenia in 1992 was 12/136 (9%) compared with 20/79 (25%) in 1966 (odds ratio 0.29; 95% confidence interval 0.13 to 0.62; P = 0.001). Adjustment for confounding by age, current hostel, and duration of unemployment by means of logistic regression produced an adjusted odds ratio of 0.22 (0.08 to 0.58). CONCLUSIONS: The prevalence of schizophrenia was lower in 1992 even after other changes in the population resident in hostels occurring between 1966 and 1992 were taken into account. The findings are not consistent with an increase in the prevalence of schizophrenia among homeless people despite a 66% reduction in adult psychiatric beds in the region during 1966-92.